Хата на Пріорці - Наумова, Н. (Народна творчість та етнографія, 2007)
In August 1859, upon coming to Kyiv, Ukrainian poet Taras Shevchenko has settled for fortnight in a small house in Kyiv suburb called Priorka. This house was preserved and the museum exhibition was arranged there. It was the last poet’s visit to Ukraine, he was 45, and on August 14 he left his native land forever. Visitors may become acquainted here with Kyiv atmosphere of the 19th century, it is reproduced in a 150/year old house, see a 400/year old oak tree under which the poet liked to have rest, get closer to the soul of Taras Shevchenko.